QMCF-MD Simulation and NBO Analysis of K(I) Ion in Liquid Ammonia - Yuniawan Hidayat; Ria Armunanto; Harno Dwi Pranowo (Indonesian Journal of Chemistry, 2018)
Ab initio of Quantum Mechanics Charge Field Molecular Dynamic (QMCF-MD) of K(I) ion in liquid ammonia has been studied. A Hartree-Fock level of theory was coupled with LANL2DZ ECP basis set for K(I) ion and DZP (Dunning) for ammonia. Two regions as first and second solvation shell were observed. In the first solvation shell at distance 3.7 (Å), K(I) ion was coordinated by four to eight ammonia molecules dominated by K(NH3)6+ species. Second shell of solvation was ranging between 3.7 Å to 7.3 Å. Within simulation time of 20 ps, the frequent exchange processes of ligands indicating for a very labile solvation structure. Four mechanism types of ligand exchange between first and second solvation shell were observed. Mean residence time of ligand is less than 2 ps confirming weak in ion-ligand interaction. Evaluation of K(NH3)6+ using natural bond orbital analysis shows that the Wiberg bond Index is less than 0.05 indicating weak electrostatic interaction of K-N.